Development and characterization of a chronic hepatitis B murine model with a mutation in the START codon of an HBV polymerase - Vanekova, L; Polidarova, M; Charvat, V; Vavrina, Z; Veverka, V; Birkus, G; Brazdova, A (Physiological research, 2023)
Chronic hepatitis B (CHB) is caused by the Hepatitis B virus (HBV) and affects millions of people worldwide. Developing an effective CHB therapy requires using in vivo screening methods, such as mouse models reflecting CHB based on hydrodynamic delivery of plasmid vectors containing a replication-competent HBV genome. However, long-term expression of HBV proteins is accompanied by production of progeny virions, thereby requiring a Biosafety Level (BSL) 3 animal facility. In the present study, we introduced a point mutation in the START codon of the HBV polymerase to develop a mouse model reflecting chronic hepatitis B infection without formation of viral progeny. We induced the mouse model by hydrodynamic injection of adeno-associated virus plasmid vector (pAAV) and minicircle plasmid (pMC) constructs into C57Bl/6 and C3H/HeN mouse strains, monitoring HBV antigens and antibodies in blood by enzyme-linked immunosorbent assay and analyzing liver expression of HBV core antigen by immunohistology. Persisting expression of viral antigens over 140 days (study endpoint) was observed only in the C3H/HeN mouse strain when using pAAV/1.2HBV-A and pMC/1.0HBV-D with pre-C and pre-S recombination sites. In addition, pAAV/1.2HBV-A in C3H/HeN sustained HBV core antigen positivity up to the study endpoint in C3H/HeN mice. Moreover, introducing the point mutation in the START codon of polymerase effectively prevented the formation of viral progeny. Our study establishes an accessible and affordable experimental paradigm for developing a robust mouse model reflecting CHB suitable for preclinical testing of anti-HBV therapeutics in a BSL2 animal facility.
Keywords: Disease Models, Animal; kodon iniciační; virus hepatitidy B; myši; Hepatitis B virus; Codon, Initiator; modely nemocí na zvířatech; Hepatitis B, Chronic; Mutation; mutace; chronická hepatitida B; Mice; Animals; Mice, Inbred C3H; zvířata; myši inbrední C3H